Purification and characterization of seven bioactive compounds from the newly isolated Streptomyces cavourensis TN638 strain via solid-state fermentation. (May 2020) - Kaaniche, Fatma; Hamed, Abdelaaty; Elleuch, Lobna; Chakchouk-Mtibaa, Ahlem; Smaoui, Slim; Karray-Rebai, Ines; Koubaa, Imed; Arcile, Guillaume; Allouche, Noureddine; Mellouli, Lotfi
Abstract: The strain TN638 was isolated from Tunisian soil contaminated with industrial wastewater and selected for its potent antimicrobial activity against the tested Gram positive bacteria: Staphylococcus aureus ( S. aureus ) ATCC 6538 and Listeria monocytogenes ( L. monocytogenes ) ATCCC 19117, and Gram negative bacteria: Agrobacterium tumefaciens ( A. tumefaciens ) ATCC 23308 and Salmonella typhimurium ( S. typhimurium ) ATCC 14028 and fungi: Candida albicans ( C. albicans ) ATCC 10231, Rhizoctonia solani ( R. solani ) ATCC 58938 and Fusarium sp. Solide-state fermentation (SSF) dry crude extract of the TN638 strain presents a strong inhibitory activity notably against the phytopathogenic microorganism A. tumefaciens ATCC 23308 and the two pathogenic bacteria S. aureus ATCC 6538 and L. monocytogenes ATCCC 19117 with a zone of inhibition of 48, 34 and 34 mm respectively. According to the morphological characteristic, the complete 16S rRNA gene nucleotide sequence determination [1492 bp deposited in National Center of Biotechnology Information (NCBI) database under the accession no. LN854629.1; https://www.ncbi.nlm.nih.gov/nuccore/LN854629.1/ ], and the phylogenetic analysis, we can deduce that our isolate is an actinomycete bacterium belonging to the genus Streptomyces and the most closely related strain was Streptomyces cavourensis ( S. cavourensis ) NRRL 2740 T (99.9%). We propose the assignment of our strain as Streptomyces cavourensis ( S. cavourensis ) TN638 strain. Work-up and purification of the strain extract using different chromatographic techniques afforded seven bio-compounds namely: Cyclo-(Leu-Pro) (1 ), Cyclo-(Val-Pro) (2 ), Cyclo-(Phe-Pro) (3 ), nonactin (4 ), monactin (5 ), dinactin (6 ) and trinactin (7 ). The chemical structures of compounds 1 –7 were confirmed by nuclear magnetic resonance (NMR) 1D and 2D spectroscopy, mass spectrometry, and comparison with literature data. The three purified diketopiperazine (DKP) derivatives (1–3), demonstrated significant antibacterial activity against A. tumefaciens ATCC 23308 and S. typhimurium ATCC 14028. The four pure macrotetrolides (4–7), exhibited strong inhibitory effect against all tested Gram positive and Gram negative bacteria notably against A. tumefaciens ATCC 23308 and S. typhimurium ATCC 14028 with a minimum inhibitory concentration (MIC) around 8 μg/mL quite similar to that of ampicillin. Thus, we propose the use of the (SSF) active extract of the S. cavourensis TN638 strain as safe biological product to control disease caused by plant pathogen A. tumefaciens . Also, the purified active molecules produced by this strain could be used in pharmaceutical field. Highlights: New Streptomyces cavourensis TN638 strain isolated from an industrial waste soil. TN638 strain was cultivated using solid-state fermentation (SSF). Seven active compounds were isolated and characterized from the (SSF) of TN638 strain. Three diketopiperazine derivatives and four macrotetrolide homologues. Biocontrol agent of A. tumefaciens and a tool in human and veterinary medicine.